2021
DOI: 10.1002/aenm.202003103
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Organic Photovoltaics: Optimal Cell Design Principles with Synergistic Parasitic Resistance and Optical Modulation Effect

Abstract: Recently, the growing popularity of indoor electronic devices has led to considerable attention on ambient energy harvesting systems. In particular, the incorporation of electronic products that harness the Internet of Things (IoT) services has spurred interest in semipermanent indoor power generation systems, owing to their numerous sensor nodes. [1][2][3][4][5] Ambient energies such as light and heat and the conversion systems to turn them into electricity have been vigorously investigated for practical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 102 publications
0
49
0
Order By: Relevance
“…Thus, developing highly transparent electrodes with improved conductivity and smooth surfaces is essential. [15,65] Goo et al constructed a transparent conducting electrode (TCE) of IOPVs by undoped low-cost ZnO. As a result, the P3HT:ICBA device based on ZnO TCE displayed a poor PCE of 0.4 % under 1 sun, while the ITO-based device showed a better PCE of 5.9 %.…”
Section: Other Methodsmentioning
confidence: 99%
“…Thus, developing highly transparent electrodes with improved conductivity and smooth surfaces is essential. [15,65] Goo et al constructed a transparent conducting electrode (TCE) of IOPVs by undoped low-cost ZnO. As a result, the P3HT:ICBA device based on ZnO TCE displayed a poor PCE of 0.4 % under 1 sun, while the ITO-based device showed a better PCE of 5.9 %.…”
Section: Other Methodsmentioning
confidence: 99%
“…For a theoretical analysis of the processes occurring in PV installations with various switching options for solar cells operating in conditions of uneven illumination, a mathematical model of a solar cell was compiled, with an accuracy sufficient for engineering calculations-not exceeding the design tolerance. Thus, the initial mathematical model describing the operation of the solar cell model is as follows [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…According to Saeed et al, many new opportunities for creating effective indoor organic photovoltaics (OPVs) for practical applications can be explored. With the introduction of different optoelectronic methods to improve device performance under low indoor lighting with varied spectra, the indoor efficiency of OPVs (for PCE > 30%) has taken a quantum leap [ 89 ]. Saeed et al demonstrated additional enhancements to dye-sensitised photovoltaic cells (DSPVs) in indoor solar applications for light energy recycling due to its outstanding light-harvesting performance under ambient lighting conditions.…”
Section: The Efficiency Improvement Of Solar Cellsmentioning
confidence: 99%